Dystonia after striatopallidal and thalamic stroke: clinicoradiological correlations and pathophysiological mechanisms. Issue 5 (1st November 1998) - Krystkowiak, P; Martinat, P; Defebvre, L; Pruvo, J P; Leys, D; Destée, A
Abstract : OBJECTIVE: To establish the pathophysiological mechanisms of striatopallidal and thalamic dystonia. METHODS: Five patients from among 26 who presented (between March 1987 and July 1996) with focal dystonia, segmental dystonia, or hemidystonia caused by a single localised vascular lesion, were selected. Patients with lesions with indefinite boundaries, and diffuse, or multiple, or large brain lesions were excluded. Three dimensional T1 weighted MRI (1.5 tesla) was performed to determine the topography of the lesions. The atlas of Hassler allowed the stereotactic localisation of the lesions to be specified exactly. RESULTS: Three patients had dystonic spasms associated with striatopallidal lesions and one with a thalamic and striatopallidal lesion. One other patient presented with a myoclonic dystonia related to a thalamic lesion. The striatopallidal lesions were located in the sensorimotor area with a somatotopical distribution. The pure thalamic lesion involved the centromedian nucleus, the sensory nuclei, and the pulvinar whereas the thalamic and striatopallidal lesion was located in the pallidonigral thalamic territory, which receives pallidonigral inputs. CONCLUSION: The striatopallidal dystonia might be the consequence of the interruption of the cortico-striato-pallido-thalamo-cortical loop induced by lesions located within the sensorimotor part of the striatopallidal complex. By contrast, it is suggested that thalamic dystonia might be caused by lesions located in the centromedian or the ventral intermediate nuclei, outside the pallidonigral territory, but leading also to a dysfunction of the cort ico - striat o - pallido - thalamo - cort ica l loop.